Faktor-faktor yang mempengaruh Kinerja Guru SMK Negeri di Kabupaten Aceh Utara. - Andi Safrizal; Apridar Apridar; Marbawi Marbawi (Universitas Malikussaleh, 2020)
This study aims to analyze the influence of the factors that affect the performanceofState Vocational School teachers in North Aceh Regency. Work ability factors, compensation for teacher performance and organizational culture, work motivation and review the mediating effects of organizational culture variables, work motivation. The data used in this study were 156 public vocational school teachers in North Aceh Regency. The data analysis method used is structural analysis with Structural Equation Modeling using the Amos Version 20 program. The results showed that the variable work ability, compensation significantly influence teacher performance as well as organizational culture variables, work motivation mediates the three exogenous variables (work ability, compensation and organizational culture, work motivation) with endogenous variables (teacher performance) partially. The recommendation that can be given is that leaders need to foster an attitude of loyalty towards the institution so that teachers have commitment, motivation and cultural values to be able to improve work for their performance. Keywords: Work ability, Compensation, Organizational culture, Work Motivation, Teacher Performance